Chagas Disease, a Triatomine Bug-Transmitted Protozoan Infection - Bethany R. Eutsey; Cameron J. Jack; Shelley A. Whitehead; Eva A. Buckner (EDIS)
Chagas disease is a potentially fatal, chronic disease caused by Trypanosoma cruzi, a protozoan parasite. It causes 6 to 8 million cases and 50,000 deaths each year. Humans and animals usually become infected with T. cruzi via triatomine bugs, also called kissing or conenose bugs, found only in the Americas. Disease transmitted by triatomine bugs generally occurs in rural areas of Mexico, Central America, and South America, but it is becoming more prevalent in non-endemic areas like the US as asymptomatic infected people move from rural to urban areas of Latin America and other regions.  In the US, approximately 300,000 people are currently infected with Chagas disease, 18,000 in Florida. Most if not all of them were infected elsewhere; local transmission of Chagas disease via triatomines in the US is rare. Awareness and understanding of Chagas disease are critical to detect and treat cases early. This publication is intended for anyone interested in learning more about Chagas disease.